Exploring beliefs around physical activity among older adults in rural Canada. Issue 1 (1st January 2016) - Schmidt, Laurie; Rempel, Gwen; Murray, Terra C.; McHugh, Tara-Leigh; Vallance, Jeff K.
Abstract : Objective: As physical activity can improve health and reduce the risk of chronic disease, it is important to understand the contributing factors to physical activity engagement among older adults, particularly those living in rural communities to assist in remaining active and healthy as long as possible. The purpose of this study was to gain a deeper understanding of the socio-ecological factors that influence or contribute to physical activity among rural-dwelling older adults in rural Saskatchewan, Canada. Methods: This qualitative description explored the perceptions of physical activity among older adults living in two rural communities in the Canadian province of Saskatchewan. Semi-structured interviews were conducted with 10 adults aged 69–94. Using content analysis techniques, transcribed interview data were coded and categorized. Results: Participants identified socio-ecological elements facilitating physical activity such as improved health, independence, and mobility as well as social cohesion and having opportunities for physical activity. The most common perceived environmental barrier to engaging in physical activity was the fear of falling, particularly on the ice during the winter months. Participants also cited adverse weather conditions, aging (e.g., arthritis), and family members (e.g., encouraged to "take it easy") as barriers to physical activity. Conclusion: Hearing directly from older adults who reside in rural Saskatchewan was determined to have the potential to improve awareness of physical activity in rural communities to support the implementation of programs and practices that will facilitate active lifestyles for older adults.